Health Education about How to Control Auditory Hallucinations in Patients with Mental Disorders in the Abepura RSJD Polyclinic Room: Penyuluhan Kesehatan Tentang Cara Mengontrol Halusinasi Pendengaran Pada Pasien Dengan Gangguan Jiwa di Ruang Poli RSJD Abepura - Naomi Frolinda Jober; Remuz MB Kmurawak (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Patients with hallucinations often experience symptoms such as talking to themselves and getting angry for no reason after returning to their families because many families do not know how to care for them. Nurses must anticipate this by increasing family knowledge about home care. This activity aims to provide an understanding of how to control auditory hallucinations in patients with mental disorders at the RSJD Abepura Polyclinic and improve the quality of service to reduce the number of patients with auditory hallucinations. Through this activity, it is hoped that public knowledge about auditory hallucination disorders and how to care for patients will increase, and efforts can be made to reduce the number of patients with auditory hallucinations at RSJD Abepura. The methods used in this activity include lectures, discussions and demonstrations on how to treat patients with hallucinations. Participants in this activity comprised 22 family members of patients undergoing treatment at the RSJD Abepura Polyclinic and three nurses at RSJD. The results of this activity show that the counselling went according to the predetermined schedule, and there was an increase in family knowledge and understanding regarding the care of patients with hallucinations. Family members who care for patients with hallucinations can now recognize the signs and symptoms and have the skills to care for these patients.